Laboratory Puzzle of Oxidative Stress, Parameters of Hemostasis and Inflammation in Hospitalized Patients with COVID-19 - Jelena Djordjevic; Vesna Ignjatovic; Vladimir Vukomanovic; Katarina Vuleta; Nevenka Ilic; Zivana Slovic; Marijana Stanojevic Pirkovic; Olgica Mihaljevic (Biomedicines, 2024)
Bearing in mind that coronavirus disease (COVID-19) is associated with a wide range of laboratory abnormalities, the aim of this study was to examine the importance of determining the parameters of oxidative stress and antioxidant protection as well as markers of inflammation and hemostasis in hospitalized patients with COVID-19. The study population included 105 patients with severe COVID-19 and 65 healthy control subjects. The parameters of oxidative stress and the activity of enzymes of the antioxidant system were determined from the obtained samples using spectrophotometric methods. Standard laboratory methods were performed for the determination of the biochemical and hematological parameters. Patients with COVID-19 showed a significantly higher level of pro-oxidative parameters (hydrogen peroxide (H2O2) and the index of lipid peroxidation in the form of thiobarbituric acid-reactive substances (TBARSs)) and a significantly lower activity of the antioxidant system (catalase (CAT)). Patients with COVID-19 had significantly higher values of inflammation parameters (C-reactive protein (CRP), procalcitonin (PCT), ratio of the number of neutrophils to lymphocytes (NLR), and ratio of the number of platelets to lymphocytes (PLR)) and parameters of hemostasis (activated partial thromboplastin time (aPTT), prothrombin time (PT), D-dimer, fibrinogen) than the control healthy subjects. In addition, changes in hemostatic parameters correlated positively with inflammatory markers in the group of patients with COVID-19. The early determination of hemostasis parameters and the parameters of inflammation can help in the prediction of poor prognosis in COVID-19 patients.